Large single crystal diamond grown in FeNiMnCo-S-C system under high pressure and high temperature conditions - 张贺 李尚升 宿太超 胡美华 李光辉 马红安 贾晓鹏 (Chinese physics B, 2016)
Large diamonds have successfully been synthesized from FeNiMnCo-S-C system at temperatures of 1255-1393 ℃and pressures of 5.3-5.5 GPa.Because of the presence of sulfur additive,the morphology and color of the large diamond crystals change obviously.The content and shape of inclusions change with increasing sulfur additive.It is found that the pressure and temperature conditions required for the synthesis decrease to some extent with the increase of S additive,which results in left down of the V-shape region.The Raman spectra show that the introduction of additive sulfur reduces the quality of the large diamond crystals.The x-ray photoelectron spectroscopy（XPS） spectra show the presence of S in the diamonds.Furthermore,the electrical properties of the large diamond crystals are tested by a four-point probe and the Hall effect method.When sulfur in the cell of diamond is up to 4.0 wt.%,the resistance of the diamond is 9.628×105 Ω·cm.It is shown that the large single crystal samples are n type semiconductors.This work is helpful for the further research and application of sulfur-doped semiconductor large diamond.